Challenges of Indonesian Democracy Post-2024 Election - Nurfebriansyah, Ahmad Rifki; Rahmatunnisa, Mudiyati; Immanuel, Glenn Kevin; Suramahardini, Karima Mahesa; Yamani, Muhammad Luthfi Thahir (JURNAL TRIAS POLITIKA, 2025)
Indonesia has experienced a decline in democracy over the past 5 years. The peak was in the 2024 Election, when political actors used their power to gain advantage in the Election. This article aims to analyze and predict how the situation of democracy in Indonesia will be in the future, especially in the next 5 years. This study uses a qualitative approach and data collection techniques with a literature review. Data analysis was carried out by observing the political symptoms that occurred and taking examples from other countries. The results of this study can be seen that the 2024 Election provides a major contraction to Indonesia's political tension. By looking at various indicators of democratization, Indonesia will experience a further decline in democracy in the future. Theoretically, this study not only enriches academic discourse on democracy and elections, but also emphasizes policy makers in formulating and maintaining Indonesian democracy in the future.